AB0583 Effectiveness and safety of short-term treatment of active rheumatoid arthritis (RA) moderate to severe with tocilizumab. (23rd January 2014) - Rodríguez-García, V.; Ordόñez, M.; Manrique-Arija, S.; Romero-Barco, C.; Nieves-Martín, L.; Ureña, I.; Jiménez-Núñez, F.; Panero, B.; Belmonte-Lopez, M.; Cano-García, L.; Coret, V.; Irigoyen, M.; et al.
Abstract : Objectives: To evaluate the effectiveness and safety of tocilizumab (TCZ) for the treatment of active RA in our department. Methods: Type of study: Prospective cohort. Inclusion criteria: RA-patients (new ACR-EULAR criteria) who have failed to at least one anti-TNF drug. Variables and Statistic: We evaluated the monthly changes of DAS28 and HAQ during the first year of treatment with TCZ using repeated measures ANOVA and survival of TCZ over the first 2 years with survival curves of Kaplan-Meier. Safety was assessed collecting adverse events, withdrawals due to safety and deaths. Results: We included 35 patients, 19 of them from clinical trials (88.6% women with a mean age of 55.3±11.1 years) with a total follow-up for 29.7 person-years, a median duration of disease of 10.0±7.3 years. Anti-CCP was positive in 22 patients (64%) and the rheumatoid factor in 31 (89%). Thirty-one (89%) had radiographic erosions and 1 patient had previous orthopedic surgery (arthroplasty of both knees). The number of previous DMARDs: 6 (17%) had received one, 11 (31%) two, 11 (31%) three, 1 (3%) four, 2 (5.7%) five, and one (3%) six DMARDs. The mean of DMARDs was 2.4±1.3 per patient. Twenty (60%) patients had taken MTX (mean dose 16.4±4.8 mg/week), 6 (17%) had received LF (mean dose 20mg/24 h) and 1 (3%) hydroxychloroquine (mean dose of 400mg/24 h). The number of previous biological therapies used was: 8 (22.9%) patients had received one, 13 (37%) two, 7 (20%) three and 6 (17%) four, which represented an average of 2, 3±1.0 per patient biologics. The DAS28 improved progressively during the first year with TCZ (F =17.8; Trace Pilai p=0.008). Although the most significant change occurred in the first month (mean difference 1.9 (95% CI =0.4 to 3.3, p=0.002, Bonferroni adjustment p=0.010) after 1 year reached an estimated mean difference of 3.1 (95% CI =1.3 to 4.8, Bonferroni adjustment p=0.002).The HAQ also improved progressively with TCZ the first 3 months (F =3.5; Trace Pilai p=0.043), but in a much slower than the DAS28 [mean difference from baseline to third month in 0.436 (95% CI = - 0056 to -0929; Bonferroni adjustment p=0.103). Twenty (57.1%) patients continued with treatment after a median of 18 months (CI 95% 11.7 to 24.2 months) which resulted in the suspension rates of 14%, 17% and 26% at 3, 6 and 12 months, respectively. The causes of withdrawal or abandonment of treatment with TCZ were: 2 (6%), infections (severe cellulitis, and conjunctivitis), 2 (6%) due to failure of efficacy, 3 (9%) for infusional reaction, 1 (3%) by asymptomatic neutropenia, 3 (9%) patient's decision, 2 (6%) due to gastrointestinal intolerance and 1 (3%) for protocol violation. Of all dropouts, only 8 patients were withdrawn due to adverse effects (including the only serious case was a right lower limb cellulitis). Conclusions: In patients with RA who have previously failed other biologic therapies, TCZ produced a rapid improvement of inflammatory activity and physical function. The rate of discontinuation due to adverse events was relatively low for this subgroup of patients (23%), and serious adverse events were unusuals. Disclosure of Interest: None Declared